Comparative study of effects of a complex fertilizer and a biostimulator on macroelement content of leaf and fruit quality on sweet cherry (Prunus avium) - Nagy, P. T.; Thurzó, S.; Drén, G.; Szabó, Z.; Soltész, M.; Nyéki, J. (International Journal of Horticultural Science, 2007)
In this study. we are partly focusing on consumer acceptance of fruit, like fruit cracking, weight and flavours, and maturation, fruit density and content of nutrients which are undelie consumer acceptance, and important equally to the growers and marketers. the results on the dynamics of N-uptake corresponded ti thephenological phases of cherry and independent on the applied treatments. Younger leaves contain more N than elder due to the effective N uptake of young leaves. Based on the measurements conducted in June, the P content of leaves was in low P supply category at the control and the Benefit treatment, while was in the lower range of optimal category at Damisol treatment. According to our measurements, the K of cherry leaves decreases continuosly until September, expcept the control at which it increased from the end of June to September. the fruit weight was increased significantly by applying Benefit PZ. the best results for fruit cracing observed at Benefit treatment too. The best result for fruit density was observed at Damisol treatment.